A thermal energy storage composite with sensing function and its thermal conductivity and thermal effusivity enhancement. Issue 12 (4th March 2019) - Lei, Hong; Fu, Chunfang; Zou, Yajun; Guo, Shiyan; Huo, Jichuan
Abstract : A composite with energy storage and temperature sensing functions is expected to enable people to manage thermal energy more efficiently. Abstract : The use of phase change materials (PCMs) to manage thermal energy is a promising and popular strategy. Many of the current thermal energy storage (TES) materials have almost no additional functions other than the TES function. Making TES materials electrically respond to temperature change and phase change processes in real time will enable people to manage thermal energy more efficiently. The present work demonstrated a novel TES composite with dual functions of energy storage and temperature sensing. The temperature change of the composite and the energy storage process can be reflected in real time by electrical signals. The TES composite with high thermal conductivity (98.1–126.4 W m −1 K −1 ) and high thermal effusivity (11.9–13.5 kJ m −2 K −1 s −1/2 ) could be prepared by simply increasing the load of PCMs. Finally, a modified parallel model was proposed to guide the further performance improvement of the TES composite.